Analisis Kompetensi Profesional dan Kinerja Dosen - Shinta Nento (IAIN Manado, 2012)
Performance of lecture in educational institutions is an interesting factor to study, because: First, the lecture is a determinant of the success of the learning process, without qualified lecturer, it is impossible to produce quality student. Second, teachers provide examples of attitudes, behavior and personality.Keywords: lecture, student, educational